The atomic layer thermopile heat flux sensor based on the inclined epitaxial YBa2Cu3O7-δ films - Chen, Xi; Tao, Bowan; Zhao, Ruipeng; Yang, Kai; Li, Zhenzhe; Xie, Tian; Zhong, Yao; Zhang, Tong; Xia, Yudong (Materials letters, 2023)
•Highly c-axis oriented YBCO films are prepared on miscut 12° LaAlO3 substrates.•The ALTP heat flux sensor with high sensitivity of 17.54 μV/(kW/m2) is obtained.•The response frequency of ALTP heat flux sensor is over 1 MHz at −3dB. The atomic layer thermopile (ALTP) heat flux sensor based on highly c-axis oriented YBa2Cu3O7-δ (YBCO) films prepared on miscut 12° LaAlO3 substrates using magnetron sputtering is achieved. Benefiting from good biaxial texture, the YBCO film maintains a large Seebeck coefficient anisotropy, so the sensitivity of the ALTP heat flux sensor reaches 17.54 μV/(kW/m2). In addition, the response frequency of the sensor is higher than 1 MHz due to the high electrical conductivity of the prepared YBCO films, which is also higher than the current maximum (650 kHz) reported in the literature. These results indicate that our ALTP heat flux sensor can realize high-frequency heat flux detection above 1 MHz.